“Flipped classroom with a MOOC” an e-learning model into a mathematics course - Lopes, Ana Paula (2017)
Nowadays, the online environment and technology tools are changing the way professors are developing and presenting course curriculum. Alongside this growth, we have assisted to the fast development of distance learning tools such as Open Educational Resources (OER) and Massive Open Online Courses (MOOCs) and the use of new teaching and learning models such the “Flipped Classroom” or “Inverted Classroom” model. This model is a pedagogical inversion of the traditional teaching paradigm: the main actions of the teaching and learning process that are used in classroom are now prepared by students previously before coming to class and provides the instructor with better opportunities for quality interaction with the students and helps students to develop a better understanding of the content and a deeper sense of community as a result of the student interaction in the course development and engagement. The purpose of this paper is to present an experimental Higher Educational plan called “Flipped Classroom with a MOOC”, within the project “Mathematics without STRESS - MOOC”, that is using flipped classroom model as a pedagogical strategy. Furthermore, it relates such strategy with active learning practices and discusses its effectiveness, investigating how the flipping affects student’s achievement and engagement. We also will present the results of a survey in which students were asked about “Flipped Learning with a MOOC” as a teaching method, using their experience from the course Mathematics Zero.